Strategi Komunikasi dan Konseling Islam untuk Mencegah Pernikahan Dini - Armila, Armila; Dwi Nopryana, Rahmah (Attractive : Innovative Education Journal, 2023)
Religious counselors play an important role in society. Islamic religious counselors act as mentors. According to Bloomfield in Gazali, Guide means to direct, guide or organize. In general, early marriage, namely marrying two people, one or both of whom are under 18 years of age, is still a serious problem in almost two-thirds of countries in the world (Yildirim et al., 2019). Although the practice of early marriage is legal, it is widely considered a violation of human rights and abuse, especially of adolescent girls. This research with the title "Islamic Counseling Strategy to Prevent Early Marriage" uses a qualitative method with a literature approach that focuses on studying reading sources. This research aims to find out how to prevent marriage using Islamic counseling strategies. A counselor is someone who can provide enlightenment to people who are experiencing spiritual problems. Religious counselors generally implement premarital counseling through information and consultation services (Albanna et al., 2019). This aims to provide information service assistance to teenagers to make appropriate and correct decisions based on the information obtained. In general, society sees people who enter into early marriage because of extramarital relationships because their behavior can no longer be controlled as a manifestation of social conditions in society. Apart from that, teenagers are psychologically not ready to face various problems that arise in marriage. This leads to domestic violence and many divorces at a young age. Disputes and divorce are common problems for young couples. In this research, marriage should be carried out at a mature and mature age. The bad impact of early marriage is in terms of biological children, and health risks for the woman or wife. Therefore, for teenagers who have not yet reached a mature and mature age, as a result, marriage will not last long. Keywords: Islamic Counseling, Early Marriage, Communication Strategy